The Effect of Pricing on Profitability in the Food And Beverage Department at Discovery Kartika Plaza Hotel - Sapitri, Ni Made Ayu Cintia (PT FORMOSA CENDEKIA GLOBAL, 2024)
A hotel is a place that provides accommodation, food, beverages, and amenities to guests, and serves as a meeting and event location. The hospitality industry, especially in the food and beverage sector, is highly competitive and vulnerable to changes in consumer demand and preferences. To maximize revenue and profitability, hotel managers must implement the right pricing strategy. Pricing is a crucial element that affects the profitability and overall financial health of the food and beverage sector. This study aims to analyze the influence of pricing on profitability at the Lobby Bar Discovery Kartika Plaza Hotel outlet, using quantitative methods. The results of the study show that there is a positive and significant relationship between pricing and profitability. Rising prices in food and beverage departments tend to increase profitability, underscoring the importance of pricing strategies in improving hotel financial performance.